Un cuarto propio portátil. - Ortiz, Marta (Confluencia: Revista Hispánica de Cultura y Literatura)
The article reviews the books "Cuando narradoras latinoamericanas narran en Estados Unidos" edited by Lourdes Vazquez, Volumes I and II.